Dupilumab shows slow, steady effectiveness for intractable prurigo in patients with atopic dermatitis. Issue 5 (20th March 2021) - Takeuchi, Satoshi; Inoue, Keiichi; Kuretake, Keisuke; Kiyomatsu‐Oda, Mari; Furue, Masutaka
Abstract: Prurigo lesions in atopic dermatitis are intractable. This single‐center, retrospective study examined dupilumab's clinical effects on intractable prurigo. Twenty adult atopic dermatitis patients (12 with prurigo, eight without) were administrated dupilumab. Its effects on itching and disease severity were examined with Numerical Rating Scale–Itch (NRS‐I), Eczema Area and Severity Index (EASI), and Investigator Global Assessment (IGA) scores; body surface areas (BSA); and thymus‐ and activation‐regulated chemokine (TARC), total immunoglobulin (Ig)E, and eosinophil levels. NRS‐I scores, EASI scores, TARC levels, and total IgE levels before dupilumab treatment were not statistically different between the prurigo and non‐prurigo groups. With dupilumab treatment, NRS‐I scores, EASI scores, IGA scores, BSA, TARC levels, and total IgE levels were significantly reduced from baseline in both groups at 1–2 months and onward, but skin symptom improvement in the prurigo group was slower than in the non‐prurigo group, as evidenced by significantly higher EASI scores, BSA, and TARC levels at several time points during the 12 months of dupilumab treatment. Prurigo patients were slower in EASI‐50 achievement and significantly lower in EASI‐90 achievement at 12 months than non‐prurigo patients. Adherence to dupilumab was not different, but total equivalent amounts of concomitant therapeutic agents (corticosteroids and tacrolimus) used during dupilumab treatment were significantly higher in the prurigo group (median, 56.2 g/week) than in the non‐prurigo group (median, 33.7 g/week). There were 2.2 adverse events per patient on average; ocular complaints were most frequent. Dupilumab was effective in treating intractable prurigo, but despite significantly greater concomitant therapeutic agent use, skin symptom improvement was slower in prurigo patients than in non‐prurigo patients.